Prevalence of Field-Collected House Flies and Stable Flies With Bacteria Displaying Cefotaxime and Multidrug Resistance. Issue 2 (19th November 2020) - Pileggi, Matthew T; Chase, John R; Shu, Runhang; Teng, Lin; Jeong, Kwangcheol C; Kaufman, Phillip E; Wong, Adam C N
Abstract: Antibiotic use in livestock accounts for 80% of total antibiotic use in the United States and has been described as the driver for resistance evolution and spread. As clinical infections with multidrug-resistant pathogens are rapidly rising, there remains a missing link between agricultural antibiotic use and its impact on human health. In this study, two species of filth flies from a livestock operation were collected over the course of 11 mo: house flies Musca domestica (L.) (Diptera: Muscidae), representing a generalist feeder, and stable flies Stomoxys calcitrans (L.) (Diptera: Muscidae), representing a specialist (blood) feeder. The prevalence of flies carrying cefotaxime-resistant (CTX-R) bacteria in whole bodies and dissected guts were assayed by culturing on antibiotic-selective media, with distinct colonies identified by Sanger sequencing. Of the 149 flies processed, including 81 house flies and 68 stable flies, 18 isolates of 12 unique bacterial species resistant to high-level cefotaxime were recovered. These isolates also showed resistance to multiple classes of antibiotics. The CTX-R isolates were predominantly recovered from female flies, which bore at least two resistant bacterial species. The majority of resistant bacteria were isolated from the guts encompassing both enteric pathogens and commensals, sharing no overlap between the two fly species. Together, we conclude that house flies and stable flies in the field could harbor multidrug-resistant bacteria. The fly gut may serve as a reservoir for the acquisition and dissemination of resistance genes.